Phosphate Removal During Conventional Hemodialysis: a Decades-Old Misconception - Rosilene M. Elias; Valeria R.C. Alvares; Rosa M.A. Moysés (Karger Publishers, 2018)
Background/Aims: Hyperphosphatemia is associated with high mortality rate in patients on dialysis. Conventional hemodialysis (HD) is a limit technique in removing phosphate (P). There is a widespread belief that P is removed mainly in the first hour of HD. The aim of this study was to certify the percentage of 1-hour removal of P as compared to the entire procedure. Methods: data from the first dialysis of the week of 21 patients (13 men, age 44±15 years), for 3 consecutive dialysis sessions were evaluated. Fresh dialysate samples were collected at 1 hour and at the end of the session from a partial spent dialysate collection method. Results: Pre dialysis serum P was 4.7±1.7 mg/dl. Reduction rate of serum P was 47.4 ± 14.3 and 45.1 ± 10.8% in 1- and 4-hour of HD, respectively (p=0.322). P removal was 194 (145, 242) mg in 1-hour (p<0.0001), which represents 25.0 ± 0.2% of the total removed during the entire HD. Patients with pre dialysis P ≥ 5.5mg/dl had higher P removal during HD than those with P < 5.5mg/dl [975 (587, 1354) vs. 776 (580, 784) mg, p=0.025], although the percentage of removal in 1 hour was not different from those with P < 5.5mg/d (24.9 ± 0.3 vs. 25.0 ± 0.1%, p=0.918). P removal during dialysis correlated with pre dialysis serum P (r=0.455, p=0.001), parathormone (r=0.264, p=0.037) and ultrafiltration volume (r=0.343, p=0.019). Conclusion: despite the P serum concentration normalizing in the first hour of hemodialysis, the removal in the same period reaches only 25% of the entire session.